The thermal probe test: A novel behavioral assay to quantify thermal paw withdrawal thresholds in mice. Issue 2 (2nd April 2016) - Deuis, Jennifer R.; Vetter, Irina
ABSTRACT: Rodent models are frequently used to improve our understanding of the molecular mechanisms of pain and to develop novel analgesics. Robust behavioral assays that quantify nociceptive responses to different sensory modalities, such has heat, are therefore needed. Here, we describe a novel behavioral assay to quantify thermal paw withdrawal thresholds in mice, called the thermal probe test, and compared it with other methods commonly used to measure heat thresholds, namely the Hargreaves test and the dynamic and conventional hot plate tests. In the thermal probe test, a slightly rounded 2.5 mm diameter metal probe that heats on contact at a rate of 2.5°C/sec, is applied to the plantar surface of the hind paw in mice at a starting temperature of ∼37°C, and the temperature at which a withdrawal response occurs, designated as the paw withdrawal temperature, is automatically recorded. The thermal probe test is effective at quantifying thermal allodynia in carrageenan-induced inflammation (paw withdrawal temperature 3 h: contralateral, 50.3 ± 0.6°C; ipsilateral, 43.1 ± 1.0°C), burns injury (paw withdrawal temperature 3 d: contralateral, 50.8 ± 0.5°C; ipsilateral, 43.2 ± 0.6°C) and after topical capsaicin (paw withdrawal temperature: vehicle control, 49.7 ± 0.6°C; capsaicin, 44.8 ± 1.2°C), giving comparable results to the Hargreaves test. In addition, the thermal probe test can detect opioid mediated analgesia in carrageenan-induced inflammation. Therefore the thermal probe test is a novel behavioral assay effective for quantifying thermal allodynia and analgesia in mouse models of pain.